Implementation of the Socata TBM-700 Aircraft as Learning Material for Live Aircraft Practical at Indonesia Civil Aviation Academy - Banyuwangi - Hadi Prayitno; Wira Gauthama (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
The increase in air transport transportation traffic after the Covid-19 subside led to increased flight frequency which also increased the need for aircraft maintenance. Good quality aircraft maintenance is also very much needed to avoid accidents due to malfunctions of all systems on the aircraft. Good quality aircraft maintenance can be achieved from qualified aircraft maintenance personnel. To produce qualified personnel, it is necessary to have a strong and deep understanding of personnel knowledge about aircraft, theoretically and practically. This research aims to carry out innovation activities in the form of implementing the Socata TBM-700 aircraft as a live aircraft suitable learning material at the Bayuwangi Aviation Polytechnic. The result of this research is an innovation of live aircraft practical learning at the Bayuwangi Aviation Polytechnic to increase the desire of active teachers at universities under PPSDMPU to be active in processing and utilizing valuable equipment available on campus so that their ability to follow the development of aviation technology can be improved.